The crucial role of neutrophil extracellular traps and IL-17 signaling in indomethacin-induced gastric injury in mice - Yujun Hou; Wen Wang; Jiangnan Ye; Luqiang Sun; Siyuan Zhou; Qianhua Zheng; Yunzhou Shi; Ying Chen; Junpeng Yao; Lu Wang; Xiangyun Yan; Renhong Wan; et al. (Scientific Reports)
Abstract The homeostasis of gastric mucosa is extremely delicate. Neutrophils, the most abundant immune cells in human circulation, are regarded crutial in the regulation of gastric mucosal immune response. Non-steroidal anti-inflammatory drugs (NSAIDs) induced gastric injury is the second major reason for gastric ulcers. The relations between neutrophils and Indomethacin-induced gastric injury are not fully understood. A mouse model of gastric injury was established using Indomethacin, followed by proteomic analysis (raw data are available via ProteomeXchange with identifier PXD058482). GO functional annotations and KEGG pathway enrichment analysis were conducted on significant differential proteins. The formation of neutrophil extracellular traps (NETs) was observed using ELISA and immunofluorescence. TEM, Western blot and Real-time PCR were applied to observe programmed death of gastric epithelial cells (GECs), and ELISA was conducted to measure levels of TNF-α and IL-1β in the gastric tissue. Deoxyribonuclease 1 (DNase 1), a NETs inhibitor, was administered intraperitoneally to inhibit NETs formation. In vitro, neutrophils were isolated from peripheral blood of mice and co-cultured with mouse GECs cell line, different dosage of Indomethacin were added to the culture dish, the levels of inflammatory factors, formation of NETs and GECs programmed death were assessed in vitro. Poly morphonuclear neutrophils (PMN) were extracted from mouse peripheral blood and single-cell RNA-sequencing (scRNA-seq) was further applied (raw data are available via Genome Sequence Archive with identifier CRA020950) to explore the intracellular mechanism of NETs formation. ELISA and immunofluorescence were performed to validate expression of IL-17 signaling pathway. After Indomethacin gavage, obvious gastric injury was observed. Proteomic analysis indicated that NETs formation played a crucial role in Indomethacin-induced gastric injury. Compared to control group, Indomethacin treatment resulted in NETs formation, elevated levels of TNF-α and IL-1β and GECs programmed death. Inhibition of NETs significantly reduced inflammatory factor levels and mitigated gastric injury caused by indomethacin. In vitro, 200 µL, 400 µL and 600 µL of Indomethacin caused excessive NETs formation in neutrophils. Besides, Indomethacin-induced NETs formation led to GECs programmed death in vitro. scRNA-seq revealed that neutrophils enrichment in the peripheral blood of Indomethacin-induced gastric injury and IL-17 signaling might be the key intracellular of NETs formation. Expressions of neutrophil IL-17R and concentration of IL-17 were significantly higher in model group. NETs formation is pivotal in Indomethacin-induced gastric injury, contributing to programmed cell death of GECs and inflammation; IL-17 signaling might be the key intracellular mechanism of NETs formation.